Eat. lift. thrive. - Lee, Sohee 1989- (Human Kinetics, 2017)
More than an exercise guide, the book Eat. Lift. Thrive. acknowledges and addresses the relationship women have with fitness and food. Popular trainer and author Sohee Lee shares her experience and strategies for overhauling mindset, eating habits, and training routines. Detailed instructions, color photos, and advice accompany Lee's nutrition tips, exercises, and 12-week program.